2021
DOI: 10.1111/ejn.15413
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging reveals neuronal microstructural changes in myalgic encephalomyelitis/chronic fatigue syndrome

Abstract: Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) patients suffer from a variety of physical and neurological complaints indicating the central nervous system plays a role in ME/CFS pathophysiology. Diffusion tensor imaging (DTI) has been used to study microstructural changes in neurodegenerative diseases. In this study, we evaluated DTI parameters to investigate microstructural abnormalities in ME/CFS patients. We estimated DTI parameters in 25 ME/CFS patients who met Fukuda criteria (ME/CFSFukuda),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 81 publications
1
40
2
Order By: Relevance
“…Importantly, a recent MRI study has suggested increased myelination in subcortical white matter regions in ME/CFS patients (Thapaliya et al, 2020). Moreover, an MRI diffusion study has shown that MD value was lower in the brainstem in ME/CFS ICC patients which is also consistent with increased subcortical myelination (Thapaliya et al, 2021). Collectively, these data suggest the fimbria volume was increased in ME/CFS ICC patients compared with HC.…”
Section: Discussionmentioning
confidence: 65%
“…Importantly, a recent MRI study has suggested increased myelination in subcortical white matter regions in ME/CFS patients (Thapaliya et al, 2020). Moreover, an MRI diffusion study has shown that MD value was lower in the brainstem in ME/CFS ICC patients which is also consistent with increased subcortical myelination (Thapaliya et al, 2021). Collectively, these data suggest the fimbria volume was increased in ME/CFS ICC patients compared with HC.…”
Section: Discussionmentioning
confidence: 65%
“…Also importantly, these MRI brain changes were associated with, and supported by, a wide range of clinical assessments, including the vital signs (36,38,43,46), sleep parameters (36,38,46), disease duration (36,37) and severity levels (37,39,41,42,44).…”
Section: Summary and Interpretation Of The Findingsmentioning
confidence: 70%
“…The studies pointed to a reduced WM volume (36)(37)(38)(39), impairments in myelination (36,38,40,43,46), reduced conduction (37,38,40,46), abnormal FC linking the brainstem and other brain regions (41,42,44), and compensatory brain changes (37,40). The research findings also demonstrated a linkage between brainstem abnormalities and other brainstem structures, highlighting myelination impairment and dysregulation underlying the disease (Table 2 and Figure 2).…”
Section: Summary and Interpretation Of The Findingsmentioning
confidence: 83%
See 2 more Smart Citations